Flipgrid for the development of english pronunciation in A2 level students. - Lainez Vera, Ileana Carolina (2022)
The present work is a research which objective was to determine the perceptions and impact of students and English teachers about the use of the web application Flipgrid as a tool to enhance the pronunciation skill of A2 level students. The population did not know anything about Flipgrid before the interviews in which Flipgrid were introduced by an interactive video and then their opinions and questions were asked. Flipgrid’s principal characteristic is to interact in the application through videos which help students to practice in first instance what they want to communicate to avoid making mistakes. The qualitative method was applied in this research which let the researcher to implement the observation method as well as techniques such as: One by one interviews to students. This research determine that students and teachers think that Flipgrid is a great way to improve pronunciations in student by the repetition method because the consequence of recording videos will be to practice first a lot of times so that the pronunciation is as good as possible. As well as this research proved that the interest of students about English increases when they add a technological resources to their learning process.